The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1093/cid/cix130
|View full text |Cite|
|
Sign up to set email alerts
|

Changing Epidemiology of Invasive Mold Infections in Patients Receiving Azole Prophylaxis

Abstract: Breakthrough invasive mold infections (IMIs) that occur during posaconazole or voriconazole prophylaxis are rare complications for which epidemiological data are lacking. This retrospective analysis comparing 24 microbiologically documented breakthrough with 66 nonbreakthrough IMIs shows a shift towards non-Aspergillus molds with a significantly increased proportion of rare multidrug-resistant molds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
96
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(113 citation statements)
references
References 11 publications
7
96
0
Order By: Relevance
“…Ten patients (21.7%) had mixed IFIs, seven patients (15.2%) had concurrent IFIs and 11 patients had breakthrough IFIs (23.9%). Of these, breakthrough IFI is well‐known risk factor for mortality in remission induction chemotherapy of AML patients and allo‐HSCT recipients . Similarly, multivariate analysis in our study showed that breakthrough IFI is an independent predictor of poor outcome (aHR = 1.99, 95% CI: 1.3‐4.41, P = .031).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Ten patients (21.7%) had mixed IFIs, seven patients (15.2%) had concurrent IFIs and 11 patients had breakthrough IFIs (23.9%). Of these, breakthrough IFI is well‐known risk factor for mortality in remission induction chemotherapy of AML patients and allo‐HSCT recipients . Similarly, multivariate analysis in our study showed that breakthrough IFI is an independent predictor of poor outcome (aHR = 1.99, 95% CI: 1.3‐4.41, P = .031).…”
Section: Discussionsupporting
confidence: 74%
“…Similar to the findings in other studies, Mucorales was the most common cause of NAIMIs followed by Fusarium spp. . The proportion of NAIMIs in total IMIs did not increase significantly within the study period, but in 2018, seven cases (four of seven are mucormycosis) were already recorded by August, and we expect that the incidence will exceed that in the previous year (Figure ).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Twenty‐three cases with confirmed invasive Rasamsonia spp. infection from the FungiScope ® registry (n = 6, 26.1%), and the literature (n = 18, 73.9%) were enrolled . One of the FungiScope ® cases (4.3%) was published previously (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…The epidemiology of invasive fungal infections (IFI) in immunocompromised children continues to evolve alongside cancer treatment regimens and hematopoietic stem cell transplant (HSCT) protocols in conjunction with selective pressure from antifungal prophylaxis strategies and environmental influences . As such, the morbidity and mortality associated with IFIs in immunocompromised children remains a major concern …”
Section: Introductionmentioning
confidence: 99%